Inside Cover: Optimized Reaction Conditions Enable the Hydration of Non‐natural Substrates by the Oleate Hydratase from Elizabethkingia meningoseptica (ChemCatChem 5/2017). Issue 5 (8th March 2017) - Demming, Rebecca M.; Otte, Konrad B.; Nestl, Bettina M.; Hauer, Bernhard
Abstract : The Cover shows the hydration of 1‐decene by oleate hydratase from Elizabethkingia meningoseptica in E. coli whole cells (depicted as a dark red "car").In their Full Paper, R. M. Demming et al. demonstrate a great increase of enzymatic productivity for the conversion of short‐chain non‐natural substrates by optimizing whole cell biotransformations adding glucose, NADH and FAD as well as applying higher temperatures. The usage of the short‐chain fatty acid dummy substrate hexanoic acid drives the hydration of the "gasoline" 1‐decene resulting in the stereoselective formation of "green" ( S )‐2‐decanol. With the alkene bound in the alkyl part of the V‐shaped binding pocket the reaction proceeds via a secondary carbocation followed by the nucleophilic attack of an activated water molecule.